Avaliações histopatológicas de brânquias e fígado de prochilodus lineatus expostos a um novo metalo-inseticida, complexo magnésio-hesperidina-fenantrolina - Sachi, Ivelise Teresa de Castro (Universidade Federal de São Carlos, 2019)
Pesticides have been continuously applied in agriculture to control insects considered agricultural pests which increases the likelihood of these products reaching the aquatic environment and affecting the biota, including fish. The present study is of great ecological importance because it evaluated the histopathological lesions and the gills and liver of curimbatá, Prochilodus lineatus (Pisces, Prochilodontidae) after 24 and 96 hours of exposure to increasing concentrations (0, 0,1, 1, 10, 100 and 1000 µg L-1) of the new metallo-insecticide [Mg(hesp)2(phen)] a Mg complex with hesperidin and phenanthroline as a chelating agent called MgHP. In the gills, the most frequent alterations were cell atrophy in the filament epithelium and lamellae, constriction / rupture / dilatation of the marginal canal of the pillar cells, lamellar epithelium hyperplasia, which occurred more frequently after exposure to 100 and 1000 µg. L-1 of MgHP. Gill change index (Iorg) increased significantly after 24 h exposure from 10 to 1000 µg L-1 MgHP and after 96 h exposure to 100 and 1000 µg L-1 MgHP. Chloride (CC) cell proliferation occurred after 96 h of exposure to 100 and 1000 µg L-1 MgHP and was more frequent in the filament epithelium. In the liver, changes in cellular structure were observed, such as hypertrophy, cytoplasmic degeneration and the appearance of intracellular cytoplasmic substances. They were more common and significant at concentrations of 100 and 1000 µg L-1 MgHP in both exposure periods (24 and 96 h). Liver Iorg increased significantly after 24 h exposure at 100 and 1000 µg L-1 MgHP concentrations and after 96 h exposure at 10, 100 and 1000 µg L-1 MgHP concentrations. The data obtained suggest that these lesions may affect the organ structure, altering the physiological functions of the exposed organism and revealed different sensitivity of the gills in relation to the liver. The gills were more sensitive in the first hours of contact with MgHP and showed recovery of gill tissue after 96 h while the liver showed greater changes after 96 h of exposure. Regarding WC, MgHP affected the density of these cells after 24 h, as a reduction was observed, which could cause a transient electrolyte imbalance. On the other hand, an increase in CC density after 96 h suggests a possible compensatory response in order to maintain the ionic balance of the animal. In general, MgHP is not toxic to P. lineatus at low concentrations, such as 0,1 and 1 µg L-1 MgHP, but is potentially toxic at very high concentrations such as 100 and 1000 µg L-1.
Histopathological evaluations of gills and prochilodus lineatus liver exposed a new methodeseticide, magnesi-hesperidine-phenantroline complex
Keywords: Citotoxidade; Prochilodus lineatus; Ecotoxicologia; Hesperidina; Pesticidas; Cytotoxicity; Ecotoxicology; Hesperidin; Pesticides; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA GERAL